ChemInform Abstract: Nafion‐H®‐Catalyzed Synthesis of Polyhydroquinolines via the Hantzsch Multicomponent Reaction. Issue 12 (14th March 2013) - Kidwai, Mazaahir; Chauhan, Ritika; Bhatnagar, Divya; Singh, Abhay K.; Mishra, Biswajit; Dey, Sharmistha
Abstract The catalyst can be reused for four runs without loss of catalytic activity.